2020
DOI: 10.1128/aac.00595-20
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Klebsiella pneumoniae ST45 Producing GES-5 Carbapenemase or GES-1 Extended-Spectrum β-Lactamase in Newborns and Infants

Abstract: GES-type extended-spectrum β-lactamases (ESBLs), like GES-1, mutate by Gly170Asn/Ser substitutions into carbapenem-hydrolyzing variants, of which GES-5 is relatively more frequent (1, 2).…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…These genes have been described on a variety of plasmid families. Noticeably, this gene family is increasingly reported with, for instance, two recent reports of GES-5-producing K. pneumoniae in Poland and GES-5-producing K. oxytoca, E. coli , and E. cloacae in UK ( 62 , 63 ).…”
Section: Minor Class a Carbapenemasesmentioning
confidence: 94%
“…These genes have been described on a variety of plasmid families. Noticeably, this gene family is increasingly reported with, for instance, two recent reports of GES-5-producing K. pneumoniae in Poland and GES-5-producing K. oxytoca, E. coli , and E. cloacae in UK ( 62 , 63 ).…”
Section: Minor Class a Carbapenemasesmentioning
confidence: 94%
“…E. coli neonatal infections and outbreaks were reported in Japan with an IMP-11 carbapenemase 37 , in China with nine NDM-5-producing ST410 strains 45 and NDM-5positive ST167 33 , in Turkey with an OXA-48-producing strain 43 , and in India with NDM-1positive clonal strains from the body of infants and the ward environment 42 . Comparatively, outbreaks in NICUs involving K. pneumoniae were globally reported, involving NICUs infections, colonizations, mobile plasmid-borne bla NDM , bla KPC , bla OXA-48 , bla IMP, bla VIM and bla GES-5 carbapenemases, and very high mortalities, making K. pneumoniae the most deadly and common neonatal MDR pathogen 13,18,25,27,28,31,36,40,41,43,44,49,50,[57][58][59][60][61][62][63] .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas several studies have reported on pregnant women colonized with CR-GNB than infected by it, there is a risk of colonized pregnant women transferring these CR-GNB to their new borns 19,[21][22][23][24] . It is therefore not surprising that numerous studies report on CR-GNB-and polymyxin-resistant Gram-negative bacteria (PR-GNB)-infected neonates than colonized ones 20,23,25,26 . Further, .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations